Writing Caption on Instagram as Media for Student’s Motivation and Writing Skill Improvement - Devy Angga Gunantar; Tatas Transinata (ETERNAL (English Teaching Journal), 2019)
This study aims to describe the use of caption on Instagram to improve students' writing skill and motivation. This research is a classroom action research (CAR). The research subject was class VIII SMP N 3 Mranggen Demak with a total of 31 students. This study was conducted in two cycles. The Pre-Test was held before the first cycle was implemented. The researcher used descriptive qualitative method to describe the use of caption on Instagram for student’s motivation and writing skill improvement. The results showed that the use of caption on Instagram can improve student’s motivation and writing skill. In the first cicle of the pre-tests that have been conducted, it was known that only 2 students (6,5%) got scores between 60 - 64. While 28 students (93%) got scores below 60. The number of students who scored above 60 increased in in the post-test I, there were 19 students with an average score of 69,5. The score of students rose significantly in the post-test II, it was found that there was a satisfactory increase in scores with the highest score of 87 and the lowest score of 66 (1 student)